1998
DOI: 10.1111/j.1545-5300.1998.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Therapy with a Multiparental/Multispousal Family

Abstract: This article examines therapy with a Bedouin-Arab family from the Negev, Israel, which consisted of 69 members: a husband, 8 wives, and 60 siblings. The husband, who lived with his youngest wife, paid little attention to his other wives and their children. There was considerable competition, hostility, and jealousy among the wives; no communication between the co-wives or the children of different wives; and a variety of behavioral and psychosocial problems among family members. I describe the varied strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 48 publications
2
77
0
5
Order By: Relevance
“…Other researchers also support the ndings that rst wives are at increased risk for depression, somaticization disorders, and other psychopatholog y (Aghanwa, Dare, & Ogunniyi, 1999;Al-Isaa, 1990;Chaleby, 1985;El-Islam, 1975). Given these ndings it is not surprising that the Arabic word for cowife is darah, meaning "one who makes trouble" (Al-Krenawi, 1998).…”
Section: Literature On Polygamous Muslim Familiesmentioning
confidence: 60%
See 1 more Smart Citation
“…Other researchers also support the ndings that rst wives are at increased risk for depression, somaticization disorders, and other psychopatholog y (Aghanwa, Dare, & Ogunniyi, 1999;Al-Isaa, 1990;Chaleby, 1985;El-Islam, 1975). Given these ndings it is not surprising that the Arabic word for cowife is darah, meaning "one who makes trouble" (Al-Krenawi, 1998).…”
Section: Literature On Polygamous Muslim Familiesmentioning
confidence: 60%
“…In particular, information about intimate partner violence in polygamous families is virtually nonexistent . This is true even though researchers provide evidence suggesting that polygamy, like family violence, is often associated with increased family stress and poor child outcomes (Al-Krenawi, 1998;AlKrenawi, Graham, & Al-Krenawi, 1997;Al-Krenawi & Lightman, 2000;Chaleby, 1988). The investigato r sought to begin to amend this gap in knowledge by examining ndings related to polygamy and wife abuse from a larger qualitative study sought abuse in the American Muslim population (Hassouneh-Phillips , 20001a, 2001b;Phillips, 1999).…”
mentioning
confidence: 94%
“…Polygamy is especially common in societies in which the child mortality rate is high and children are valued for their labor and for the emotional support and security they provide their parents in old age. In some countries (especially in Africa, where most polygamy research has been conducted), a family needs many children to provide the labor force required for subsistence farming (Al-Krenawi, 1998;Owuamanam, 1984).…”
Section: Social Aspects Of Polygamymentioning
confidence: 99%
“…It has been reported that children from polygamous families experience higher rates of marital conflict, family violence and family disruptions (see Al-Krenawi, 1998;Elbedour, Bart, & Hektner, 2000). These problems are commonly associated with maladjustment (Buehler & Gerard, 2002).…”
Section: Impact Of Polygamy On Childrenmentioning
confidence: 99%